Volume 1: Large Bore Engines; Fuels; Advanced Combustion; Emissions Control Systems 2014
DOI: 10.1115/icef2014-5460
|View full text |Cite
|
Sign up to set email alerts
|

Gas and Particle Emissions From a Diesel Engine Operating in a Dual-Fuel Mode Using High Water Content Hydrous Ethanol

Abstract: Diesel engines running in a dual-fuel fumigation mode using injection of a high volatility fuel into the intake air and direct injection of diesel fuel can reduce NOX and particulate matter emissions. Fuels such as methanol, hydrogen, gasoline, and anhydrous ethanol have been studied as fumigants; however there has been less published regarding the use of high water content hydrous ethanol. Current production of ethanol yields anhydrous (200 proof) ethanol with no water content. The distillation and dehydratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Overall, soot emissions decreased drastically, reaching near 90% reduction from CDC levels at high FEF. This result is somewhat contrary to our earlier hydrous ethanol PFI work [1][2][3] which showed that soot emissions remained high even at significant FEF. With reformed ethanol, as FEF increased, engine combustion was more premixed with significantly less directly injected diesel.…”
Section: Engine Performance and Emissionscontrasting
confidence: 99%
See 2 more Smart Citations
“…Overall, soot emissions decreased drastically, reaching near 90% reduction from CDC levels at high FEF. This result is somewhat contrary to our earlier hydrous ethanol PFI work [1][2][3] which showed that soot emissions remained high even at significant FEF. With reformed ethanol, as FEF increased, engine combustion was more premixed with significantly less directly injected diesel.…”
Section: Engine Performance and Emissionscontrasting
confidence: 99%
“…However, the high load condition experienced only a minor increase before decreasing, indicative of the high CE seen during this condition, providing further evidence that ISR operation is most beneficial at high loads. Unlike our previous work with hydrous ethanol [1][2][3], no unburned ethanol was present at engine outlet conditions. Instead, THC emissions consisted mainly of methane, depicted in Figure 6 and smaller amounts of acetaldehyde and formaldehyde.…”
Section: Engine Performance and Emissionsmentioning
confidence: 86%
See 1 more Smart Citation
“…From the literature, no information can be gained on the impact of hydrous ethanol gasoline blends on particulate matter emissions from a port injection gasoline engine. Several investigations have studied the effects of hydrous ethanol fuel on PM emissions from diesel engines [31][32][33], and they found that hydrous ethanol was effective in reducing PM emissions from diesel engines. Hence, research on PM emissions for the hydrous ethanol gasoline blends is needed.…”
Section: Introductionmentioning
confidence: 99%